Back Cover Image, Volume 116, Number 11, November 2019. Issue 12 (31st December 2020) - Kuhn, Alexandre; Le Fourn, Valérie; Fisch, Igor; Mermod, Nicolas
Abstract : The cover image is based on the Original Article Genome‐wide analysis of single nucleotide variants allows for robust and accurate assessment of clonal derivation in cell lines used to produce biologics by Alexandre Kuhn et al., https://doi.org/10.1002/bit.27534 .